Analysis Of Higher Order Thinking Skills Indicators on Physics Student Worksheet Class XI Semester II - Nurhayati, Nurhayati (Department of Physics Universitas Negeri Padang, 2024)
One of the key contents of the implementation of the 2013 program is the application of learning-oriented learning to forge higher-order thinking skills. Observational results show that the student worksheet used in public high schools in Padang city is the student worksheet made by the teachers and the student worksheet released by the publisher. It is yet to be determined whether all student worksheet already contain the HOTS components required by the program. Therefore, a study on Component Analysis of Higher Order Thinking Skills (HOTS) was carried out during the student worksheet XI Semester II Physics Class at SMAN Padang City. This research is a descriptive research with a qualitative approach. The population is all worksheets for class XI senior high school physics students in semester II which are used by 16 public high schools in Padang City. The sample is student worksheet Physics SMA Class XI Semester II with the most 3 student worksheet. The research data used the student worksheet presentation analysis instrument and data collection techniques through documentation studies. Based on the analysis, it can be concluded that the Semester II Class XI Physics student worksheet used by SMAN in Padang City is of the low-facilitation and non-facilitation category. Search results for the HOTS component of student worksheet questions are in the least favorable category. The question sheets with the highest HOTS component are those with the RC-IP code student worksheet XI/II in the moderately supported category. While other student worksheet are of the low-facilitation and non-facilitation type